Solidary Neighbors? The Involvement of Middle-Class Communities in the Governance of Security and Disorder in Brazil - Lopes, Cleber (Journal of contemporary criminal justice, 2022)
This study explores how residents govern security in two middle-class neighborhoods in Londrina, the fourth largest city in southern Brazil. Utilizing nodal governance theory, it analyses a security program called Solidary Neighbor (Vizinho Solidário, in Portuguese) in both neighborhoods, in place since the early 2010s. Document analysis, direct observation, and interviews with 26 respondents comprising mostly residents, but also police officers, sex workers, and homeless people, were conducted to assess how the program works and what implications it has for the governance of public spaces. The findings show that the Solidary Neighbor program functions as a community governance node oriented toward reducing criminal opportunities with the use of technologies to monitor outsiders and displace sex workers and homeless people. The article concludes that particularly in contexts such as in Brazil, bottom-up security initiatives have the potential to produce hostile and exclusionary public spaces.